Customer Segmentation Based on Rfm Analysis as The Basis of Marketing Strategy Case Study of Crude Palm Oil Product in Palm Oil Industry - Syahfitri, Fenny; Heikal, Jerry (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
Nowadays so many palm oil companies sell the product to potential buyer to maximize their revenue, so they need to understand the customer's data better in all aspects. Segmenting the customers according to their data became extrem important in this context. This study aims to explore customer segmentation using RFM (Recency, Frequency, and Monetary) analysis as a basis for developing an effective marketing strategy for Crude Palm Oil (CPO) products in the palm oil industry. In this paper, i used data of crude palm oil sales database that obtained from digital platform named Customer Relationship Management (CRM) System and Auction by E-commerce involving 56 buyers by 2.499 transactions. After the scoring and data processing, the number of customers for each RFM Score is obtained, then the Monetary group is segmented which is divided into 27 Labels and grouping to 11 (eleven) Labels of Buyer’s Company, Engaged (8), Loyal (9), Potential (9), Affair (14), Broke Up (3), No Hurt Feeling (1), Disappointed (2), Agony (1), Broken Heart (3), Hurt Feeling (3) and Lost Feeling (3). By using RFM analysis, it can effectively creating a marketing strategy to increase the status of potential customer to the loyal customer to increase the corporate’s revenue and to improve corporate’s value added.